A New Visual Transient Elastography Technique for Grading Liver Fibrosis in Patients With Chronic Hepatitis B. Issue 2 (June 2021) - Ren, Xinping; Zhang, Lu; Xia, Shujun; Chen, Zhijie; Zhou, Wei; Ji, Ri; Zhou, Jianqiao; Lin, Yanyan; Zhan, Weiwei
Abstract : Abstract: Liver fibrosis is evaluated to assess the prognosis and guide the treatment of chronic hepatitis B (CHB). To compare the efficiency of 2 transient elastography techniques for grading liver fibrosis in CHB: visual transient elastography (ViTE) with real-time image guidance and FibroScan (FS) with no image guidance. All of the CHB patients in this study underwent both FS and ViTE examinations. The final diagnosis was based on the histological findings of a liver biopsy. According to the severity of liver fibrosis (based on the Scheuer criteria), the area under the receiver operating characteristic curve values for diagnostic efficiency were calculated for the 2 elastography techniques. This study enrolled 227 patients (79 [39.1%] women; mean age, 45.8 ± 16.8 years). The ViTE and FS liver elasticity measurements were highly correlated with liver fibrosis stage ( r = 0.852 and r = 0.813, respectively). The area under the receiver operating characteristic curve value was larger for ViTE compared with FS, with respect to differentiating liver fibrosis stage, but not significantly ( P > 0.05). The ViTE and FS can be used to detect and stage liver fibrosis. ViTE, easier and quicker to perform with superior interoperator reproducibility, is a stable and reliable elastography technique that benefits from real-time visual guidance.